STRATEGIES AND PRAGMATIC EQUIVALENCE OF THE WORD FUCK TRANSLATION IN THE WOLF OF WALL STREET MOVIE - Nizar Ibnus (Universitas Sarjanawiyata Tamansiswa, 2021)
The choice of strategy for translating the word fuck in The Wolf of Wall Street movie has its own impact on the equivalence of pragmatic meanings in the target text. This study aims to explain: (1) form, pragmatic function, and translation strategy of the word fuck, and (2) the implication of the word fuck translation strategy on pragmatic equivalence in The Wolf of Wall Street movie. The words of fuck were identified from the both English and Indonesian subtitles. Then, the data were categorized and the implications were investigated. The results indicate that there are 506 words of fuck which are classified into three forms, namely: interjection, emphasizer, and expletive slot filler. The functions conveyed by these taboo words are: catharsis, abusive, and social. These taboo words were translated using omission (72.9%), cultural substitution (15.0%), neutral words (11.5%) and loan word (0.6%). The omission and the neutral word strategy largely eliminated the function of the word fuck, whereas the loan word and cultural substitution strategy were able to maintain the function of the word fuck. However, the very large percentage of use of the omission strategy makes the translation results lose much of its pragmatic function and emotive value. Keywords: Translation strategy, taboo word, pragmatic equivalence, the wolf of wall street movie